2010
DOI: 10.1103/physrevb.82.193201
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen donors inSnO2studied by infrared spectroscopy and first-principles calculations

Abstract: Hydrogen is a potentially important source of n-type conductivity in oxide materials. We have investigated hydrogen in tin oxide ͑SnO 2 ͒, a wide-band-gap semiconductor with applications as a transparent conductor and in gas sensors. Infrared ͑IR͒ spectroscopy and electrical measurements indicate that hydrogen binds to a host oxygen atom and increases the conductivity. First-principles calculations confirm that interstitial hydrogen acts as a shallow donor ͑H i + ͒. Our calculations also indicate that H i + di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 30 publications
4
45
2
Order By: Relevance
“…Results from the previous study by Hlaing Oo et al 27 differ from the above, and O-H absorption was reported only for E⊥c. Furthermore, the lines at 3334.2 and 3343.2, while present, were weak in the spectra reported by Hlaing Oo et al and were not discussed in their paper.…”
contrasting
confidence: 55%
See 4 more Smart Citations
“…Results from the previous study by Hlaing Oo et al 27 differ from the above, and O-H absorption was reported only for E⊥c. Furthermore, the lines at 3334.2 and 3343.2, while present, were weak in the spectra reported by Hlaing Oo et al and were not discussed in their paper.…”
contrasting
confidence: 55%
“…1 and 4 show that annealing SnO 2 in an H 2 ambient at 700 °C produces strong free-carrier absorption in addition to a 10 number of O-H vibrational lines, in agreement with other recent work. 27 SnO 2 and ZnO have similar electron masses and mobilities 19,38,39 suggesting that calibrations of the free-carrier absorption determined previously for ZnO, 32, 36, 37 also annealed in an H 2 ambient, can be applied approximately to the freecarrier absorption spectra measured for SnO 2 at room temperature. 40 With this approximate calibration, the free-carrier absorption shown in the "as-treated" spectrum in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations